2000
DOI: 10.1101/gad.14.3.360
|View full text |Cite
|
Sign up to set email alerts
|

RecA protein-dependent R-loop formation in vitro

Abstract: The RecA protein of Escherichia coli, which has crucial roles in homologous recombination, DNA damage repair, induction of the SOS response, and SOS mutagenesis, was found to catalyze assimilation of complementary RNA into a homologous region of a DNA duplex (R-loop). The reaction strictly requires a region of mismatch in the duplex, which may serve as a nucleation site for RecA protein polymerization. The optimum conditions for the assimilation reaction resemble those for the previously studied RecA protein-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Our observation that ONs with a LNA or 2′-OMe RNA backbone can hybridize to the outgoing strand of a short synaptic complex suggests that transcripts in the cell could participate in a similar reaction and that the hybridized RNA could serve as a primer for the initiation of DNA synthesis. This pathway for RNA uptake is distinct from the recently described inverse strand exchange reaction (19,20). In that reaction, dsDNA in a RecA or Rad51 filament strand exchanges with a homologous single-stranded DNA or RNA.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our observation that ONs with a LNA or 2′-OMe RNA backbone can hybridize to the outgoing strand of a short synaptic complex suggests that transcripts in the cell could participate in a similar reaction and that the hybridized RNA could serve as a primer for the initiation of DNA synthesis. This pathway for RNA uptake is distinct from the recently described inverse strand exchange reaction (19,20). In that reaction, dsDNA in a RecA or Rad51 filament strand exchanges with a homologous single-stranded DNA or RNA.…”
Section: Discussionmentioning
confidence: 86%
“…The extended structure of dsDNA that is bound to a recombinase facilitates several unconventional strand exchange reactions. For example, the inverse of regular strand exchange occurs when dsDNA occupies the primary binding site and ssDNA or ssRNA occupies the secondary binding site of a RecA or Rad51 filament ( ). If dsDNAs occupy both binding sites of the filament, reciprocal four-strand exchange between the two duplexes can sometimes be observed ( , ).…”
mentioning
confidence: 99%
“…Accumulating genetic evidence in E. coli has suggested that one form of recombination-dependent replication known as constitutive stable DNA replication is achieved by RecAfacilitated joint molecule formation between an RNA transcript and the bacterial chromosome (49). Biochemical support for this idea comes from studies showing RecA can promote annealing of an RNA oligonucleotide with a free single-stranded DNA or with a preformed single-stranded loop in a DNA heteroduplex, (50) and furthermore, can perform an inverse strand exchange reaction between a DNA heteroduplex and a homologous single-stranded RNA (51,52). All of these pairing reactions performed with RNA are much less efficient than with DNA, presumably due to steric hindrance encountered during protein-promoted extension of the RNA phosphodiester backbone in preparing for intermolecular association (53).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that the RecA recombinase of Escherichia coli can promote formation of DNA−RNA hybrids. 257,258 Yeast RNA-templated DSB repair is strongly dependent on the recombinase Rad52, a fundamental protein in DNA repair by HR. 169,259 However, knockout of the RAD52 gene, while reducing the frequency of DSB repair by RNA by a factor of 10, does not eliminate DSB repair by RNA, indicating that Rad52-independent RNA-templated DSB repair mechanisms do exist.…”
Section: How Does Rna-templated Dsb Repair Work?mentioning
confidence: 99%
“…Instead, the sensitivity to RNase H activity indicates that DNA–RNA hybrids must form to transfer information from RNA to DNA. Previous work showed that the RecA recombinase of Escherichia coli can promote formation of DNA–RNA hybrids. , Yeast RNA-templated DSB repair is strongly dependent on the recombinase Rad52, a fundamental protein in DNA repair by HR. , However, knockout of the RAD52 gene, while reducing the frequency of DSB repair by RNA by a factor of 10, does not eliminate DSB repair by RNA, indicating that Rad52-independent RNA-templated DSB repair mechanisms do exist. These results in yeast are supported by in vitro experiments corroborating the ability of the Rad52 protein to catalyze the annealing of RNA to DNA .…”
Section: Rna-templated Dna Repair In Yeast and Mammalsmentioning
confidence: 99%